2014
DOI: 10.1099/mic.0.072520-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and virulence variation in an environmental population of the opportunistic pathogen Aspergillus fumigatus

Abstract: Environmental populations of the opportunistic pathogen Aspergillus fumigatus have been shown to be genotypically diverse and to contain a range of isolates with varying pathogenic potential. In this study, we combined two RAPD primers to investigate the genetic diversity of environmental isolates from Manchester collected monthly over 1 year alongside Dublin environmental isolates and clinical isolates from patients. RAPD analysis revealed a diverse genotype, but with three major clinical isolate clusters. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 100 publications
(169 reference statements)
2
13
0
Order By: Relevance
“…Analysis of SNPs among all publicly available sequenced isolates (>100 total; 95 unique isolates included in the present study) across a global range of clinical and environmental sources shows considerable genetic diversity, consistent with previous reports of genetic variance in A. fumigatus (22). Given that we are unable to know how, when, and where ISSFT-021 and IF1SW-F4 initially colonized the ISS, it is curious that both strains bare the closest relationship to the strains Af300 and JN10 (27) (Fig.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Analysis of SNPs among all publicly available sequenced isolates (>100 total; 95 unique isolates included in the present study) across a global range of clinical and environmental sources shows considerable genetic diversity, consistent with previous reports of genetic variance in A. fumigatus (22). Given that we are unable to know how, when, and where ISSFT-021 and IF1SW-F4 initially colonized the ISS, it is curious that both strains bare the closest relationship to the strains Af300 and JN10 (27) (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…While a detailed analysis of specific SNPs in the ISS isolates was beyond the scope of our present study, the number total SNP differences of ISSFT-021 and IF1SW-F4 compared to Af293 were within the range of documented variance among existing sequences of environmental A. fumigatus strains (Fig. 1), suggesting that, without a more detailed analysis, the ISS strains likely reflect genetic diversity already found on Earth (22). …”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…It is important to note that in the above mentioned studies in which discrepancies concerning IL-1 dependency arise, different A. fumigatus strains and morphotypes were used [29, 47, 49]. Interestingly, it is rapidly emerging that different strains of A. fumigatus can induce both dramatically different inflammatory responses [51, 52] and differing levels of virulence in vivo [52–54]. Interestingly, Rizzetto et al showed that the CEA10 isolate of A. fumigatus induced the greatest inflammation, which corresponded with its increased growth in immune competent mice [52].…”
Section: Role Of Il-1α and Il-1β During Invasive Fungal Infectionsmentioning
confidence: 99%